Capabilities and limitations of tracing spatial temperature patterns by fiber‐optic distributed temperature sensing. Issue 3 (29th March 2013) - Rose, Liliana; Krause, Stefan; Cassidy, Nigel J.
Key Points: Qualitative and quantitative accuracies of FO‐DTS surveys vary with signal‐size Detection accuracy of cold signals is higher than of similar seized warm signals Impact of small‐scale signal‐size / ‐ strength on observation is not unambiguous Abstract : [1] Increasing numbers in interdisciplinary applications of Fiber‐optic Distributed Temperature Sensing (FO‐DTS) call for a quantitative assessment of the limitations and uncertainties of this new technology. This study conducts controlled laboratory experiments to analyze the qualitative (signal size and location) and quantitative (signal intensity) accuracies of FO‐DTS surveys of temperature signals higher and lower than ambient temperature, ranging from well above to critically below the FO‐DTS sampling interval. Our results reveal that qualitative and quantitative accuracies of FO‐DTS measured temperatures critically decline with decreasing signal size, in particular for signals near the spatial sampling interval. Decreasing detection accuracy risks the masking of real temperature variation in highly dynamic systems. The resulting potential ambiguity of interpretations of signal size, intensity, and absolute location will have to be considered in future experimental design and interpretation of FO‐DTS surveys.